2017
DOI: 10.1002/1878-0261.12028
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of ID4 promotes a CRPC phenotype with constitutive AR activation through FKBP52

Abstract: Castration‐resistant prostate cancer (CRPC) is the emergence of prostate cancer cells that have adapted to the androgen‐depleted environment of the prostate. In recent years, targeting multiple chaperones and co‐chaperones (e.g., Hsp27, FKBP52) that promote androgen receptor (AR) signaling and/or novel AR regulatory mechanisms have emerged as promising alternative treatments for CRPC. We have shown that inactivation of inhibitor of differentiation 4 (ID4), a dominant‐negative helix loop helix protein, promotes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…FKBP4 was found to be associated with major depressive disorder (Binder et al, 2004;Tatro et al, 2009a,b) and might be critical to early steps in neuronal differentiation (Quintá and Galigniana, 2012), chemotropic guidance of neuronal growth cones (Shim et al, 2009), and regulating neuroprotective activities with calcium channels (Ruan et al, 2008). It was also reported in malignancies like prostate cancer (Bhowal et al, 2017;Joshi et al, 2017) and breast cancer (Ostrow et al, 2009). CCNY knockout can inhibit glioma cell proliferation (Xu et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…FKBP4 was found to be associated with major depressive disorder (Binder et al, 2004;Tatro et al, 2009a,b) and might be critical to early steps in neuronal differentiation (Quintá and Galigniana, 2012), chemotropic guidance of neuronal growth cones (Shim et al, 2009), and regulating neuroprotective activities with calcium channels (Ruan et al, 2008). It was also reported in malignancies like prostate cancer (Bhowal et al, 2017;Joshi et al, 2017) and breast cancer (Ostrow et al, 2009). CCNY knockout can inhibit glioma cell proliferation (Xu et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…This hormone receptor activity makes FKBP52 an interesting target in hormone-driven tumors like prostate cancer, colorectal adenocarcinomas, breast cancer, and myelomas (Storer et al, 2011; Storer Samaniego et al, 2015). Recently, Joshi et al were able to prove an interaction between FKBP52 and inhibitor of differentiation 4 (ID4) in castration-resistant prostate cancer (CRPR) in vitro (Joshi et al, 2017). In this type of cancer, prostate cancer cells adapt to the androgen-depleted environment of the prostate.…”
Section: Fkbp51 and Fkbp52mentioning
confidence: 99%
“…The analysis of needle prostate biopsies in humans revealed that FKBP52 is indeed a useful and reliable biomarker of prostate cancer [91]. Its close-related partner FKBP51 is also overexpressed in this type of cancers and shows the ability to stimulate AR activity [93,94,95], the immunophilin being itself a product of the AR activity [96]. This generates a harmful feedback circuit that is worsened by the fact that FKBP51 impairs the biological activity of the GR.…”
Section: Immunophilins In Steroid Receptor-related Cancermentioning
confidence: 99%